Digital Learning Co-Creation: A Conceptual Study between University and Learning Hub in Underdeveloped Urban Areas - Eliza, Mona; Afifi, Abdullah A; Arifin, Nor Anisa; Azami, Evan (Journal of Regional Development and Technology Initiatives, 2024)
This article presents a conceptual co-creation model of digital learning between universities and learning hubs in organizing online lectures as a strategy to increase literacy access in underdeveloped urban areas. The background of this study comes from initial observations conducted at Darulfunun Payakumbuh, a community-based institution that has facilitated students from various universities to take online lectures with the support of study rooms, connectivity, and mentoring. In the context of limited infrastructure and learning facilities at home, a collaboration between higher education institutions and digital learning centers such as Darulfunun is a potential solution to overcome the gap in access to education. This study uses a conceptual approach by combining the principles of co-creation (co-initiation, co-design, co-delivery, co-reflection) and the Customer Satisfaction framework, especially the expectation-perception-reaction model towards digital learning services. The discussion is directed at the design of shared facilities, adaptive collaboration mechanisms, and measuring student satisfaction with the quality and access to online lecture services. This study produces a conceptual model that can be used as a reference for further research and development of community-based higher education policies, with implications for increasing digital literacy and equality of access to higher education in marginalized areas.